Improvised apparatus for producing and detecting electromagnetic waves - Truzan, Merlinda C. 1947- (1977)
The purpose of the study was to construct and develop an improvised apparatus for producing and detecting electromagnetic waves. The study involved the use of discarded and locally available materials as substitute for the the induction coil, vibrator, the metal ball, and the detector. Results have shown that a discarded ignition coil can be recycled as an induction coil; a thin0-springy iron plate with pointed end can substitute for the metal ball where sparks may be produced; the receiver can be constructed by thousands of turns of copper wire coiled in an air-core; and the current induced in the receiver can be detected using a neon bulb.
Vita.
Thesis (M.A. Physics Education)--University of the Philippines, Diliman.
Keywords: Physics -- Study and teaching -- Philippines -- Butuan City (Agusan del Norte); Electromagnetic waves; Physical instruments